Antonio Sorge, Legacies of Violence: History, Society and the State in Sardinia, Toronto, University of Toronto Press, 2015, pp. 194 - Heatherington, Tracey (Anuac, 2016)
Book review of Antonio Sorge, Legacies of Violence. History, Society and the State in Sardinia, Toronto, University of Toronto Press, 2015, pp. 232.Recensione di Antonio Sorge, Legacies of Violence: History, Society and the State in Sardinia, Toronto, University of Toronto Press, 2015, pp. 194